Comparison of the efficiencies of esophageal manometry, vector volume analysis and esophagus pH monitoring in the diagnosis of gastroesophageal reflux - Aydın, Emrah (Turk Pediatri Ars, 2015)
AIM: In this study, we aimed to compare the superiorities of esophageal manometry, vector volume analysis and 24-hour pH meter studies in showing gastroesophageal reflux disease. MATERIAL AND METHODS: The files of the patients who presented to pediatric surgery and pediatric gastroenterology outpatient clinics of our hospital with suspicious gastroesophageal reflux disease between 2011 and 2012 and who were investigated were examined and 21 patients whose investigations had been completed were included in the study. The patients were evaluated by treatment method and were divided into three groups as Group 1 who were followed up with medical treatment, Group 2 in whom surgical intervention was performed and Group 3 who were not treated. Chi-square test was used in evaluation of the categorical variables, Kruskal Wallis test was used in comparison of the mean values between the groups and Dunn test was used in subgroup analyses when Kruskal Wallis test was found to be significant. A p value of <0.05 was considered statistically significant. RESULTS: Thirteen of 21 patients included in the study were female and eight were male. The mean age of the patients was 5.71 years (one-16 years). In the 24-hour pH monitoring study, the mean reflux index was found to be 48.7% in Group 1, 42.4% in Group 2 and 28.3% in Group 3. In esophageal manometry studies, the pressure difference at lower esophageal sphincter (LES) was found to be 13,4 cm H(2)O in Group 1, 31.8 cm H(2)O in Group 2 and 4.3 cmH(2)O in Group 3. In vector volume analyses, the mean vector volume was calculated to be 96.01 cm(3) in Group 1, 2 398.9 cm(3) in Group 2 and 196.3 cm(3) in Group 3. In the 24-hour pH monitoring study, a statistically significant difference (p<0.05) was found in terms of showing reflux, whereas statistical significance could not be shown in terms of need for surgical treatment or need for medical treatment in any other method (p>0.05). CONCLUSIONS: Twenty-four-hour pH monitoring was found to be efficient in making a diagnosis of gastroesophageal reflux disease, whereas esophageal manometry and vector volume analyses were not found to be efficient.